Increasing Danger in Business After the Pandemic: Adaptation of the Quiet Quitting Scale to Turkish - Tayfun Arar; Gülşen Yurdakul (Istanbul Business Research)
The awareness created by COVID-19 in people has caused a difference in their thoughts about work-life balance. People who experienced remote working with the idea that they understood the meaning and importance of life better began to resign in this process. Those who cannot resign and have to continue working in their current jobs have started to show quiet quitting behavior, which can pose a risk within the organization, especially in extraordinary situations such as crises. To prevent undesirable results, it is important to measure the level of employees’ potential behavior to identify the problem first. This research consists of two main studies. In the first study, the quiet quitting scale developed by Anand et al. (2024) was adapted into Turkish. In this context, a survey was conducted on 414 employees. A one-dimensional scale consisting of six items was obtained by performing necessary reliability and validity analyses (CMIN/DF; 1.672, GFI; .979, AGFI; .944, CFI; .990, NFI; .975, TLI; .981, RMR; .051, RMSEA; 0.057). In the second study, the obtained scale was considered within the scope of the Conservation of Resources Theory, and its validity was tested in two separate models with 287 different employees in which organizational commitment and its subdimensions were the antecedents and job performance and its subdimensions were outcomes.